Analisis Kemampuan Pengetahuan Konseptual Peserta Didik SMA Kelas XI Di Kabupaten Lombok Tengah Mata Pelajaran Biologi Dilihat Dari Lokasi Sekolah - Safitri, Temi Ainul (REFORM : Jurnal Pendidikan, Sosial, dan Budaya, 2021)
This study aimed to describe the cognitive conceptual ability of learners on biology subject at the eleventh grade of senior high school students on the even semester. This research was included in the survey research. This research was conducted in central Lombok regency in terms of rural and urban school location. The sampling technique used purposive sampling. The population in this study was all schools in central Lombok regency with the sample used were students in high school schools in the city and in the village. This research method used descriptive survey method. The technique of collecting data used a test. Then, the data analysis used Mann-Whitney U test. The results of this study were significant differences (significance value of 0,000 <0.05) on the conceptual ability of high school students based on the location of rural and urban schools. Based on the average results with the Mann Whaitney test on the ranks table were that the mean of the urban schools was the number of 144.39 and the average of rural schools outcome amounted to 105.38. Thus, the location of the school can affect the level of ability of learners.